Comparison of the electrochemical properties of hematite thin films prepared by spray pyrolysis and electrodeposition. Issue 7 (August 2015) - Vanags, Martins; Šutka, Andris; Kleperis, Janis; Shipkovs, Peteris
Abstract: This manuscript reports differences between the photoelectrochemical (PEC) activity of hematite (α-Fe2 O3 ) photoanodes produced by cathodic electrodeposition (ED) and spray pyrolysis (SP) methods. Both methods yield nanostructured polycrystalline α-Fe2 O3 thin films without additional impurity phases. However, α-Fe2 O3 produced by ED is characterised to have better crystallinity and higher porosity, which was confirmed by XRD and SEM analysis. Owing to this, α-Fe2 O3 obtained by ED generates a photocurrent that is 2.5 times higher than α-Fe2 O3 thin films prepared by SP. Furthermore, the influence of the thickness of the α-Fe2 O3 thin films on the flat-band potential position was investigated. Mott–Schottky measurements revealed flat-band potential shifting to more negative values, closer to the value of water red-ox potentials, providing the possibility to use these films for efficient water splitting.